Heart antibodies in cardiomyopathies. - Trueman, T (1981)
The reported frequency of circulating heart reactive antibodies in cardiomyopathies has varied and their significance is unknown. In this study such antibodies were sought in patients with primary congestive and hypertrophic cardiomyopathies and other heart diseases. Standard "single sandwich" and the more sensitive "double sandwich" indirect immunofluorescence techniques failed to disclose a significant difference between any cardiomyopathic group and controls in repeated experiments. With both techniques results were subject to considerable method-specific artefacts and observer variation. No published work associating heart antibodies detected by immunofluorescence methods with cariomyopathies adequately takes these into account.